2016
DOI: 10.1371/journal.pone.0158632
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity Effects of Spiramycin In Vitro and In Vivo

Abstract: The effects of spiramycin on adipogenesis and high fat diet (HFD)-induced obesity were investigated. Potential mechanisms contributing to these effects were elucidated. The inhibitory effect of spiramycin on adipocyte differentiation was assessed using 3T3-L1 preadipocyte cells, in which several parameters involved in AMPK signal pathways and lipid metabolism were examined. To further investigate the pharmacological effects of spiramycin in vivo, we examined several obesity-related parameters in HFD-induced ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Studies on the effects of this drug on adipogenesis have revealed that spiramycin inhibits adipogenesis both in vivo and in vitro . Spiramycin at con-centrations of 2.5-20 μmol/L inhibited the adipogenic differentiation of 3T3-L1 pre-adipocyte cells in a dose-dependent manner, which was further confirmed in the high-fat diet-induced obese mice model[69]. It is reported in the above study that salinomycin at 10 μmol/L does not affect the osteogenic differentiation potential of human bone marrow-derived MSCs.…”
Section: Effects Of Various Antimicrobial Agents On Adipogenic Differmentioning
confidence: 61%
“…Studies on the effects of this drug on adipogenesis have revealed that spiramycin inhibits adipogenesis both in vivo and in vitro . Spiramycin at con-centrations of 2.5-20 μmol/L inhibited the adipogenic differentiation of 3T3-L1 pre-adipocyte cells in a dose-dependent manner, which was further confirmed in the high-fat diet-induced obese mice model[69]. It is reported in the above study that salinomycin at 10 μmol/L does not affect the osteogenic differentiation potential of human bone marrow-derived MSCs.…”
Section: Effects Of Various Antimicrobial Agents On Adipogenic Differmentioning
confidence: 61%
“…In this study, we confirmed the possibility of applying an old weapon, spiramycin, to various inflammatory diseases, the new enemy. Spiramycin has been shown to exhibit anti-bacterial, anti-viral, and anti-parasitic activities [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. However, no study has reported the anti-inflammatory potential of spiramycin in LPS-induced macrophage RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Third is the potential of spiramycin as an anti-obesity treatment and cosmeceutical ingredient. Kim et al reported that HFD-induced obese mice administered with spiramycin showed significant reductions in weight gain, serum leptin levels, adipose tissue mass, and liver lipid accumulation, which effectively attenuated high-fat diet (HFD)-induced obesity and hepatic steatosis by inhibiting adipogenesis [ 12 ]. In addition, according to our unreported results, spiramycin has potential as a whitening cosmeceutical ingredient by inhibiting melanin production in B16F10 melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3T3-L1 cells are fibroblast-like preadipocytes, which differentiate into adipocytes, and are commonly used to study adipogenesis [35]. Master transcriptional regulators of adipogenesis, including PPARγ, C/EBPα, and SREBP1c, are necessary modulators of target gene expression that are involved in adipocyte differentia-tion at various stages [36]. C/EBPs consists of six different proteins, C/EBPα, C/EBPβ, C/EBPγ, C/EBPδ, C/EBPε, and C/EBPζ, that are widely expressed in numerous tissues and regulate many cellular processes, including cell cycle, inflammation, differentiation, metabolism, and cellular proliferation [37,38].…”
Section: Discussionmentioning
confidence: 99%